A global human rights approach to pre-service teacher education on LGBTIs. Issue 3 (27th May 2019) - Jones, Tiffany
ABSTRACT: Pre-service teacher education on LGBTI rights and inclusion is impacted by multiple conflicting education governance provisions carrying different risks and duties for teachers. Pre-service teacher education has an international reach – catering to both international pre-service teachers and domestic pre-service teachers destined for careers and travel abroad. This paper argues that pre-service teacher education efforts focussing solely on local education treatments of LGBTI rights may leave pre-service teachers sorely underprepared for the differing education contexts they may encounter. The article proposes that teacher educators should communicate relevant international human rights legislation provisions and education policies on LGBTIs. It provides overviews of LGBTI identities, laws and policies, and data across multiple contexts based on key informant interview data and desk-based research. It argues that some sources on LGBTIs are unreliable and informed by broader disruptive geopolitical efforts, and suggests why and how to train pre-service teachers to avoid them.